Disentangling the Amyloid Pathways: A Mechanistic Approach to Etiology - Malmberg, Maja; Malm, Tarja; Gustafsson, Oskar; Sturchio, Andrea; Graff, Caroline; Espay, Alberto J.; Wright, Anthony P.; El Andaloussi, Samir; Lindén, Anders; Ezzat, Kariem (Frontiers in Neuroscience, 2020)
Amyloids are fibrillar protein aggregates that are associated with diseases such as Alzheimer’s disease, Parkinson’s disease, type II diabetes and Creutzfeldt–Jakob disease. The process of amyloid polymerization involves three pathological protein transformations; from natively-folded conformation to the cross-β conformation, from biophysically soluble to insoluble, and from biologically functional to non-functional. While amyloids share a similar cross-β conformation, the biophysical transformation can either take place spontaneously via a homogeneous nucleation mechanism (HON) or catalytically on an exogenous surface via a heterogeneous nucleation mechanism (HEN). Here, we postulate that the different nucleation pathways can serve as a mechanistic basis for an etiological classification of amyloidopathies, where hereditary forms generally follow the HON pathway, while sporadic forms follow surface-induced (including microbially-induced) HEN pathways. Furthermore, the conformational and biophysical amyloid transformation results in loss-of-function (LOF) of the original natively-folded and soluble protein. This LOF can, at least initially, be the mechanism of amyloid toxicity even before amyloid accumulation reaches toxic levels. By highlighting the important role of non-protein species in amyloid formation and LOF mechanisms of toxicity, we propose a generalized mechanistic framework that could help better understand the diverse etiology of amyloid diseases and offer new opportunities for therapeutic interventions including replacement therapies.